Comparative Analysis of RNA Extraction Quality Using TRIzol-Based and Non-TRIzol Methods in Endometriosis Lesion Tissue - Ocktariyana Ocktariyana; Bertha Octarina; Shungai Mutiara Aini; Refai Refai; Irsan Saleh; Fatimah Usman; Adnan Abadi; Asmarinah Asmarinah (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2026)
Ribonucleic acid (RNA) is a crucial molecule in gene expression analysis, yet its isolation from solid tissues, such as endometriotic lesions, poses significant challenges due to complex tissue structure and high RNase activity. TRIzol is a widely utilized reagent for RNA extraction, known for its efficacy in lysing cells and stabilizing RNA. This study aimed to compare the quality of RNA extracts from endometriotic lesion tissue samples using TRIzol-based and non-TRIzol-based methods. A quasi-experimental design was employed, involving a control group and an experimental group, with non-randomized sample allocation. A total of 28 samples were analyzed in both the control and treatment groups. The results demonstrated that TRIzol treatment significantly increased the median RNA concentration from endometriotic lesion tissues, yielding 288.6 ng/μL compared to 118.2 ng/μL in the non-TRIzol group (p=0.001). Furthermore, there was a significant difference between TRIzol and non-TRIzol groups in RNA purity based on the Å260/280 ratio (median: 2.00; p-value:0.024). However, there wasn’t a significant difference in the Å260/230 ratio (median: 2.11; p-value: 0.247). In conclusion, these findings indicate that while TRIzol extraction provides higher RNA yield, the non‑TRIzol method ensures slightly superior sample purity, supporting its reliability for downstream transcriptomic analyses.